The linkage of perceptions of online loans and financial literacy to interest in online loans with lifestyle as a moderating variable - Elida Florentina Sinaga Simanjorang; Anita Sri Rejeki Hutagaol; Emul Mulyana; Bactiar Rifai; Asep Syiarudin (Trigin Publisher, 2023)
The development of digital information technology encourages faster information dissemination, making it easier for everyone to get access to the desired service. One impact is the convenience of financial institutions (non- banks) to provide online loan services. This institution also has the convenience of attracting its customers. This convenience has also led to the large number of official and unofficial online lending arrangements which often mislead their customers. The perception of convenience without thinking about risk is one of the reasons, the presence of financial literacy socialization is expected to minimize the negative impact of this online loan. The research was conducted on 100 Generation Z respondents in Pandeglang district, Banten province. Statistical analysis using SEM-PLS software version 4.0. Research shows that there is a positive influence between perceptions of interest in online loans, while the hypothesis put forward is that there is a negative influence between the two variables